Mean platelet volume and D-dimer as predictors for complicated community-acquired pneumonia in hospitalized children - Rehab Elmeazawy; Osama Toema; Amira Mobarak (SpringerOpen, 2024)
Abstract Background Community-acquired pneumonia (CAP) is one of the primary causes of child mortality and morbidity. The primary objective of our research was to assess the value of mean platelet volume (MPV) and D-dimer levels in predicting complicated community-acquired pneumonia in hospitalized children. Methods This observational retrospective study gathered medical data from the electronic medical records of children diagnosed with CAP who were admitted to the Pediatric Pulmonology Unit between December 2021 and December 2022. Results This study included 154 pediatric patients. Their age at presentation was 4.15 ± 3.60 years. A comparison of patients with complicated CAP and non-complicated CAP revealed a statistically significant decrease of MPV in the complicated CAP group than in the non-complicated group (p = 0.016). The D-dimer level was significantly higher in the complicated CAP 3.42 ± 3.02 µg/ml compared than in the non-complicated 1.63 ± 2.04 µg/ml, p = 0.002). Low MPV and increased D-dimer were powerful indicators of complicated CAP (OR 0.577, p = 0.021, OR 1.419, p = 0.003). Conclusion The current study highlights that low MPV and high D-dimer levels can be useful predictors of pulmonary complications of CAP in children. However, prospective observational studies are needed to evaluate the changes in these predictors during the disease and assess the time needed for normalization.